Out-of-school suspensions in U.S. public schools: relations with chronic teacher absenteeism - Fabes, Richard A.; O'Rourke, Holly; Catherine, Evandra; Shen, Zuchao; McDonald, Ashley (Frontiers in Developmental Psychology, 2023)
Out-of-school suspensions (OSS) put students at risk for an array of negative social and academic outcomes. Rates of use of OSS vary considerably from one school to another, however, school-level characteristics have not been studied extensively. The purpose of this study was to examine the degree to which chronic teacher absenteeism predicted overall rates of OSS as well as racial/ethnic disparities in its use. Although research has established that teachers are one of the most significant school-based factors affecting student success and learning, they need to be present in the classroom for students to derive these benefits. Using a national sample of public schools in the U.S, the findings confirmed that schools with higher rates of chronic teacher absenteeism also had higher rates of use of suspension. Moreover, higher proportions of chronic teacher absence in a school were related to greater disparities in rates of suspensions for Black relative to white students. It was concluded that chronic absenteeism represents a significant risk factor that is related to the use of OSS with students in a school.